Pengaruh Discovery Learning dengan Pendekatan Culturally Responsive Teaching terhadap Kemampuan Pemahaman Matematis - Reza Dwi Yanuar; Edi Hidayat; Sri Tirto Madawistama (J-PiMat : Jurnal Pendidikan Matematika, 2026)
This study aimed to investigate the effect of the Discovery Learning model integrated with a Culturally Responsive Teaching (CRT) approach on students’ mathematical understanding of systems of linear equations in two variables. An experimental method with a posttest-only control group design was employed. Data were collected using an essay-type test of mathematical understanding developed based on established indicators of mathematical comprehension. The population consisted of all ninth-grade students of SMP Negeri 8 Tasikmalaya in the 2025/2026 academic year, comprising 11 classes. Samples were selected through simple random sampling, resulting in class IX-J as the experimental group and class IX-H as the control group. Data analysis involved prerequisite tests of normality and homogeneity, followed by hypothesis testing using an independent samples t-test. The results showed that the Discovery Learning model integrated with the CRT approach had a significant effect on students’ mathematical understanding compared to Direct Instruction with a scientific approach. The t-test yielded a calculated value of 4.189 exceeding the critical value of 1.672, leading to the rejection of the null hypothesis. The coefficient of determination indicated that the treatment accounted for 23.23% of the variance in students’ mathematical understanding.Keyword: CRT, Discovery Learning, Mathematical Understanding Ability.